CONVERGENCE IN CORPORATE GOVERNANCE: THE CASE OF CHINA AND INDIA - A. Majumdar (BRICS Law Journal, 2020)
China and India face similar challenges in maintaining their aggressive rates of economic growth. While both countries attained economic independence in the late 1940s, each followed a different path in terms of growth. China preferred to open up its economy to foreign direct investment much earlier and only in recent times has it turned towards domestic capital. India, on the other hand, began by attempting to develop local talent and shifted its focus to foreign participation in 1991. This paper examines the politicoeconomic background and the resultant corporate governance paths undertaken by each of these countries. These paths, while diverse, lead to a convergence. In particular, given the nature of concentrated shareholdings in Chinese and Indian companies, by the State in China and by family promoters in India, the second agency problem and the requisite protection of minority shareholders assume considerable importance in both jurisdictions. However, given the nature of corporate governance norms having been transplanted from advanced economies to emerging economies, this convergence may not be suitable or even desirable. This paper posits that emerging economies such as China and India ought to develop and implement corporate governance norms that are separate from those of advanced economies to combat the unique issues arising out of shareholding patterns at home.